DETERMINANT OF LAW BIRTH WEIGTH: REVIEW ARTICLE - Legawati, Legawati (JOURNAL OF RESEARCH IN PUBLIC HEALTH SCIENCES, 2019)
Introduction: Low Birth Weight (LBW) is one of the main public health problems in newborns that affects newborns with many health problems, such as hypoglycemia, hypothermia, mental retardation, physical and neurological development problems. As a result, the risk of high mortality in LBW infants. According to 2014 WHO estimates, 4.53% of total deaths in Ethiopia were caused by LBW. Globally, 15 to 20% of newborns are LBW; 13% in sub-Saharan Africa and 15.9% in developing countries (Armenia, Cambodia, Colombia, Indonesia, Jordan, Nepal, Pakistan, Tanzania, Uganda and Zimbabwe). As a result, LB is a tremendous burden on the political, social, economic and health systems in developing and developed countries. Therefore, at the end of 2025, the World Health Organization sets a target of 30% to reduce LBW. Objective: to identify determinants and risks for the LBW. Method: PubMed, Web of Science, Cochrane Library, and Google Scholar are sought. Fun plot and Egger regression test are used to see publication bias. I-square statistics were applied to test the heterogeneity of the study. The model of the effect of random variance was applied to estimate national prevalence and effect size of related factors. Subgroup analysis was carried out based on region, research design, and year of publication. Results: The prevalence of low birth weight infants in Ethiopia remains high. This review can help policy makers and programs to prevent the birth of babies.